Bank Stock Returns And Financial Volatility: A MGARCH-M Modeling - Hooy, Chee Wooi (2002)
This study examines the sensitivity of commercial bank stock excess returns to the volatility level and financial risk factors, measured by interest rate risk and exchange rate risk across the recent Asian financial crisis horizon, via Multivariate GARCH in Mean (MGARCH-M) model. Application of time varying risk model into bank's stocks is of special importance as both the financial risk factors and the stock returns volatility varied substantially in the Asian recent financial crisis. Generally, MGARCH (p, q)-M process captures almost all of the linear dependence in both the returns' mean, and the residual's variance of the fitted model. The results of this study further show that in Malaysia, the pattern of risk sensitivity is about the same for both large and small banks during the crisis period. Unlike studies from developed markets, the portfolio partition in the case of Malaysia did not provide significant difference on bank stocks risk exposures. Before the crisis, the excess returns generally followed white noise process and the residual variances have strong GARCH effects, indicating that the current volatility of bank's stocks persisted from past periods. The banks equity returns and its volatility fails to show a pricing relationship with its volatility level and financial risk factors, due to close regulatory framework set by government on the economy system. During the crisis period, commercial banks' hedging activities, and government interventions in both the financial factors, had stabilized the bank stocks' volatility. This can be explained because during crisis, bank stocks' returns followed a white noise process while the GARCH effects in the variances equation are very weak. Furthermore, when the market is in disorder, bank's stocks performance could be better explained by the overall market's performance and the annoyances in the market. After the financial control, due to the unexpected interest rate policy and the merger announcement, large bank's returns are increasingly sensitive to its own volatility. The stock's prices of small banks are only exposed to interest rate volatility but its magnitude is relatively larger than large banks'. The forced consolidation program has stongly affected the confidence of investors on the performance of small banks as the small bank's volatility is significantly driven by the interest rate volatility.It seems that the recent crisis had affected the exposure of bank's stocks to risk. Investors seem to be more actively engaged as reflected by the significant risks concern in bank's stocks pricing. The control and announced consolidation program fail to regain investors' full confidence in bank's stocks. Nevertheless, in view of long run welfare, the increasing risk concern in bank's stocks will contribute to the development of the domestic banks. When the market prices the stocks, the prices will reflect the true value and the performance of the banks. This will further enhance the market efficiency on banking stocks and contribute to future expansion, by ensuring an effective intermediation of fund to the efficient banks.